Information Frictions and Learning Dynamics: Evidence from Tax Avoidance in Ecuador - Albrecht Bohne; Jan Sebastian Nimczik (Institute of Labor Economics (IZA), 2018)
We show how experience and dynamic learning processes reduce the obstacles to optimization imposed by information frictions when individuals newly enter the formal sector economy. Most importantly, we provide causal evidence on the exact mechanisms through which individuals learn about the functioning of government programs. To this aim, we exploit novel and rich administrative data on the universe of taxpayers in Ecuador and the introduction of generous tax deduction policies. Key to the identification of information transmission is exogenous worker mobility between firms. We find that the spread of information is driven by mobility of managers and tax experts.
Keywords: D83; H24; H26; H32; O17; 330; learning; tax avoidance; information frictions; taxation and development; bunching; behavioral responses to taxation